Research Progress of the Functional Nucleic Acid Techniques in GMO Detection - Ying Shang; Kunlun Huang; Wentao Xu (Journal of DNA And RNA Research, 2017)
Functional nucleic acids are a kind of nucleic acid sequences with special functions, which can specifically bind with the target substances or catalyze the reactions. Many target, including mycotoxins, small RNA, heavy metal ions and DNA segment, can bind to particular selected oligonucleotides, and then realized the detection. The uses of functional nucleic acids to detect the genetically modified organism (GMO) have been pursued using different approaches. Meanwhile, the flanking sequence, which was the most specific target in the GMO detection, was also usually separated with the help of functional nucleic acid. During the detection, the functional nucleic acid provided superior sensitivity, specificity and success rate compared with the traditional methods. In this report, we described different functional nucleic acids used in the GMO detection, they were classified based on their structures, and some of them were developed in our lab. The principle, structural composition, advantage, and the comparisons of the functional nucleic acids were reported. Considering most of the functional nucleic acids are fluorescently-labeled, in order to reduce the cost, more and more functional nucleic acids without labeling are under research.
Keywords: Functional nucleic acid